2013
DOI: 10.1155/2013/418320
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Visual Evoked Potentials in the Assessment of Visual Field Defects in Primary Open-Angle Glaucoma: A Review

Abstract: Visual evoked potentials is an important visual electrophysiological tool which has been used for the evaluation of visual field defects in primary open-angle glaucoma and is an appropriate objective measure of optic nerve function. Significant correlations between the magnitude of the VEP parameters and MD of Humphrey static perimetry suggest that the impaired visual cortical responses observed in glaucoma patients can be revealed by both electrophysiological and psychophysical methods. In addition, the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The VEP has been employed to identify and monitor glaucomatous nerve damage and the components of the flash‐VEP are reduced in glaucoma . Our findings from the flash‐VEP recording showed that both amplitude and latency of the main P2 component were affected by I/R injury.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The VEP has been employed to identify and monitor glaucomatous nerve damage and the components of the flash‐VEP are reduced in glaucoma . Our findings from the flash‐VEP recording showed that both amplitude and latency of the main P2 component were affected by I/R injury.…”
Section: Discussionmentioning
confidence: 76%
“…The VEP has been employed to identify and monitor glaucomatous nerve damage 25,26 and the components of the flash-VEP are F I G U R E 6 In vitro co-culture of BM-derived Sca-1 + cells with retina explants decreased retinal cell apoptosis. Retina explants were cocultured with BM-derived Sca-1 + or Sca-1 − cells under normoxia and hypoxia conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they are all subjective tests, which need patients’ input and are easily influenced by patients’ comprehension, emotion and psychological state. Visual evoked potential, as an objective visual functional test, provides a unique tool to assess the visual functional impairment in glaucoma patients [1012]. Specifically, PVEP has been shown increasing abnormalities as glaucomatous optic nerve damage progressed [13].…”
Section: Introductionmentioning
confidence: 99%
“…Visual evoked potential is an important electrophysiological objective tool which can be used for the evaluation of visual field defects in primary open-angle glaucoma. 3 The severity of visual field defect can lead to delay in the neural conduction from the retina to the visual cortex. The positive correlation between MD, PSD and VEP latencies in cases of glaucoma confirms it.…”
Section: Discussionmentioning
confidence: 99%
“…1 The diagnostic criteria of POAG is a triad of raised IOP, characteristic visual field defect and cupping of optic nerve head with presence of open angles and absence of any secondary cause of raised IOP. 2,3 Visual evoked potential (VEP) is an important diagnostic tool that can be used to study the optic nerve head and visual field changes in cases of POAG. Increased latencies and decreased amplitude of VEP both have been documented in cases of glaucoma.…”
Section: Introductionmentioning
confidence: 99%